Inhibition of β-Catenin/CREB Binding Protein Signaling Attenuates House Dust Mite-Induced Goblet Cell Metaplasia in Mice - Kuchibhotla, Virinchi N. S.; Starkey, Malcolm R.; Reid, Andrew T.; Heijink, Irene H.; Nawijn, Martijn C.; Hansbro, Philip M.; Knight, Darryl A. (Frontiers in Physiology, 2021)
Excessive mucus production is a major feature of allergic asthma. Disruption of epithelial junctions by allergens such as house dust mite (HDM) results in the activation of β-catenin signaling, which has been reported to stimulate goblet cell differentiation. β-catenin interacts with various co-activators including CREB binding protein (CBP) and p300, thereby regulating the expression of genes involved in cell proliferation and differentiation, respectively. We specifically investigated the role of the β-catenin/CBP signaling pathway in goblet cell metaplasia in a HDM-induced allergic airway disease model in mice using ICG-001, a small molecule inhibitor that blocks the binding of CBP to β-catenin. Female 6-8-week-old BALB/c mice were sensitized to HDM/saline on days 0, 1 and 2, followed by intranasal challenge with HDM/saline with or without subcutaneous ICG-001/vehicle treatment from days 14-17, and samples harvested 24 hours after the last challenge/treatment. Differential inflammatory cells in bronchoalveolar lavage (BAL) fluid were enumerated. Alcian blue (AB)/Periodic acid–Schiff (PAS) staining was used to identify goblet cells/mucus production, and airway hyperresponsiveness (AHR) was assessed using invasive plethysmography. Exposure to HDM induced airway inflammation, goblet cell metaplasia and increased AHR, with increased airway resistance in response to the non-specific spasmogen methacholine. Inhibition of the β-catenin/CBP pathway using treatment with ICG-001 significantly attenuated the HDM-induced goblet cell metaplasia and infiltration of macrophages, but had no effect on eosinophils, neutrophils, lymphocytes or AHR. Increased β-catenin/CBP signaling may promote HDM-induced goblet cell metaplasia in mice.